P. K. Page’s “Conversation”: a Dialogue between Painting and Poetry = “Coversation” de P. K. Page: um diálogo entre a pintura e a poesia - Renaux, Sigrid (Revista de Letras, 2008)
This work analyzes P.K.Page’s poem “Conversation”, which concerns the remembrance of a dialogue between the Canadian poet and the Israeli ambassador Arie Aroch, while both were engaged in painting a canvas in her studio on Estrada da Gávea, in Rio de Janeiro. By way of a stylistic approach – foregrounding the recurrence of a specific vocabulary related to painting, of formal and pictorial frames (the picture within a picture) and of images suggestively symbolical –, the analysis will reveal that, in spite of the informality of the dialogue enhanced by the use of free verse lines, the poem actually becomes a dialogue between the art of painting and the art of poetry. Keywords: Canadian poetry. Stylistics. Aesthetics. O presente trabalho faz uma leitura do poema “Conversation” (1997), de P.K.Page, que reproduz a lembrança de um diálogo entre a poeta canadense e o embaixador israelense Arie Aroch, enquanto ambos pintavam um quadro no estúdio da Estrada da Gávea, no Rio de Janeiro. Através de uma abordagem estilística – salientando a recorrência de um vocabulário específico da pintura, de molduras formais e pictóricas (o quadro dentro de um quadro) e de imagens sugestivamente simbólicas – a análise irá revelar que, apesar do tom informal do diálogo ressaltado pelo emprego de versos livres, o poema na realidade se torna um diálogo entre a arte da pintura e a arte da poesia. Palavras-chave: Poesia canadense. Estilística. Estética.